Me Ajudem
a- 9(x +3+2 x) =7 (x - 10 + 8)=
b-12( x - 5 + 10 x) =5 (x-30)=
c-13 (2 x - x + 10)=
d-14 + 3 (x -10 + 5)=8 + 2(x - 10 - 3 x)=
e-10 + 3 x = - 5 (x + 10 -7)=

Por Favor é Para Daqui a Pouco

1
g) x - 1/3 + 4x + 1/6 = 5/10
x - 1 + 4x + 1 = 5/10 * 3*6
5x = 5/10 * 18
x = 5/10 * 18/5
x = 5*18 / 10*5
x = 90 / 50
x = 9/

Respostas

2013-09-17T10:03:56-03:00
a)- 9(x +3+2 x) =7 (x - 10 + 8)=
   -9x+5x=7x-2
   -4x+5x5x
   -4x+25x
   21x
Moço ei não é um - ali depois do A é um tracinho me ajuda em todas
g) x - 1/3 + 4x + 1/6 = 5/10
x - 1 + 4x + 1 = 5/10 * 3*6
5x = 5/10 * 18
x = 5/10 * 18/5
x = 5*18 / 10*5
x = 90 / 50
x = 9/